A survey of practice patterns in the use of laryngeal mask by pediatric anesthesiologists. Issue 11 (6th August 2015) - Patel, Anuradha; Clark, Scott R.; Schiffmiller, Moshe; Schoenberg, Catherine; Tewfik, George; Lerman, Jerrold
Summary Background Laryngeal mask is frequently the airway device of choice in routine general anesthesia for many procedures in children. Several studies have described the use of laryngeal masks in unconventional situations. This survey was undertaken to assess how laryngeal masks are being used by pediatric anesthesiologists. Method The 40‐question electronic survey using SurveyMonkey™ was sent to 2740 members of the Society for Pediatric Anesthesia (SPA). This survey assessed the age, work environment, types of practice, and training levels, as well as clinical situations in which the practitioners use laryngeal masks across different pediatric age groups. Results Seven hundred and forty‐three (27.1%) responses were obtained. The use of laryngeal mask increased as the patient age increased in nearly every queried situation. The practitioners routinely utilize laryngeal masks in a variety of challenging scenarios, such as in patients with a recent upper respiratory infection, in the difficult airway, remote locations, and long‐duration surgeries. A small percentage of pediatric anesthesiologists use laryngeal masks in laparoscopic surgery and prone position procedures. Conclusion Pediatric anesthesiologists are using laryngeal masks in both routine and challenging/unconventional situations. Although many of the uses for laryngeal masks are not explicitly stated in the manufacturer guidelines, literature and current practice support the use of laryngeal masks in several of these scenarios.